COMPARING TECHNIQUES, TO OBTAIN THE GLOBAL ATTACTOR ITS HAUSDORFF DIMENSION AND FRACTAL OF THE REACTION DIFFUSION EQUATIONS IN UNBOUNDED DOMAIN - Moya Lázaro, Nancy Rosa (2009)
In this paper we study the asymptotic behavior of solutions of reaction diffusion equations.